(untitled) (Orfeu, 2023)
This article presents compositional and interpretative aspects of the work Gravidade Zero (2020), for drum set and tape, approaching the musical discourse from two perspectives: the temporal structure layer and the sonic/timbral layer. The work grants great freedom to the drummer to create musical materials that will, in line with the tape, fill in the temporal structure specified in the score. Both layers can be subdivided into musical aspects created by the composer, on the one hand, and aspects derived from the drummer’s performance, on the other. The aim of the work was to turn the rhythmic patterns performed in the drum set (which normally have an accompanying function) into the main element of the musical discourse. The article also presents a discussion on the interpretative strategies adopted by the drummer, highlighting the use of polymetries and polyrhythms. We conclude by presenting some analyses carried out using audio descriptors. By comparing two sections of identical lengths and metric structures, we demonstrate how the use of different sonorities/timbres in the sections helped to generate musical variety, thus fostering the interest of the listener.